"Agrarian Reform Village" Pematang Johar Village: Access to Reform to Realize Land-Based Community Empowerment - Medaline, Onny; Nadirah, Ida; Lubis, Muhammad Syukran Yamin (Jurnal Cakrawala Hukum, 2023)
The National Land Office of Deli Serdang Regency has Pematang Johar Village which is used as a location for a land-based community empowerment program. Agricultural land in Pematang Johar Village is used as a life asset and becomes the basic capital of the community to improve welfare and realize an increase in per capita income of recipients of agrarian reform access. This study analyzes the form of technical activities for managing assets and access to agrarian reform. So that it will provide an overview of the form of land-based community empowerment that has been implemented by the BPN of Deli Serdang Regency. The method used is a conceptual approach with a descriptive case study that analyzes the implementation of access reform. Based on the results of the study, Pematang Johar Village, Deli Serdang Regency is an area designed as an "Agrarian Reform Village" and is designated as a pilot project with an access reform model in the form of corporate farming. Technically, the Agrarian Reform Access Arrangement activity uses an empowerment strategy approach based on an analysis of social mapping, problems, potential, situations, and directions of needs that will be the targets of community land distribution activities. How to cite item: Medaline, Onny, Ida Nadirah, and Muhammad Syukran Yamin Lubis. "Agrarian Reform Village" Pematang Johar Village: Access to Reform to Realize Land-Based Community Empowerment.â€ Jurnal Cakrawala Hukum 14 no. 3 (2023):322-332. DOI: 10.26905/idjch.v14i3.11309.